The Role of The Indigenous Knowledge System of The Community Dayak In Water Management Kahayan River: Review of Local Wisdom Perspective - R. Sally Marisa Sihombing (Iapa Proceedings Conference, 2018)
Watershed Management (DAS) is expected in the future to provide a framework towards achieving sustainable development. Watershed management itself is a renewable resource of plants, soil and water in order to provide maximum and sustainable benefits. Watershed management is a human effort in controlling the reciprocal relationship between natural and human resources with all its activities in the watershed. The goal of watershed management is to foster the sustainability and harmony of ecosystems and to increase the utilization of natural resources for humans in a sustainable manner (RLPS, 2002) In relation to watersheds, the Central Kalimantan region is an area whose surface is a river flow. This is evident from the availability of the lanting house as a community residence on the shore of the Kahayan river. There is also the presence of Handil or Saka within the Kahayan river area which is a sluice gate or known as tabat in managing the river, as well as the culture of catching fish which is called Mihing as a tool for Dayak people in fishing. From the previous research, the dissertation research (Sihombing 2014: 89) states that there is a local culture produced by local Dayak people in managing the river which is an innovation for the community to fulfill their daily lives. (Sihombing, 2016; 223) This is what is called the Indigeneous Knowledge System, which is the knowledge system of the local community which is considered as an originality or originality of the knowledge of the community. Departing from this thought, the research that has been carried out from the dissertation research derivative then the methodology used is qualitative ethnography with the aim of further exploring and studying the indigenous knowledge system in the Dayak community in managing the river, and this is what makes the concept of indigeneous knowledge system play a role in river management is seen from a review of the perspective of local wisdom that has been ingrained. This paper is also a continuation of the results of research that has also been carried out, which found that there is a correlation or relationship between innovation and knowledge systems of local communities, is a study of Public Administration in examining more broadly the implementation and understanding of social science in formulating policies that lead to fulfillment of community life needs and management.